Fenomena Childfree di Kalangan Selebritas Perspektif Maqasidy dan Utilitarianisme - Sagita, Insharie Amarylis; Santoso, Lukman (Institut Agama Islam Negeri (IAIN) Kediri, 2024)
Changes in economic structure and ideology have an impact on the way modern humans view life and family. One of the paradigms shifts that has emerged is the decision of family couples to postpone pregnancy or even not to have children. This phenomenon is even starting to spread among Indonesian society, pioneered by several public figures. This article aims to explain the childfree phenomenon from the perspective of Maqasid Syari'ah Abu Ishaq Al-Syatibi and Utilitarianism. This research is classified as qualitative research using netnographic studies using several sources on social media platforms. Supported by a library research approach. The results of the research that has been carried out show that from the perspective of Maqasid Syari'ah Abu Ishaq Al-Syatibi the phenomenon of childfree is contrary to the concept of the main goal of Maqasid Syari'ah Abu Ishaq Al-Syatibi because looking after offspring is classified as the main goal where this phenomenon eliminates the nature of a woman, and This is also not in line with the purpose of marriage. In contrast to the utilitarian perspective that childlessness has an impact on reducing the number of human populations and abandoned children throughout the world, on the other hand, women have the right and freedom to choose whether to have children or not. If the decision not to have children does not harm other people and no party feels disadvantaged, the decision can be accepted. The contribution of the results of this research can be used as material for consideration in formulating policies in responding to the childfree phenomenon so that it is more open and wiser from various points of view.